Smoking Cessation after a Cancer Diagnosis: A Cross-Sectional Analysis in the Setting of a Developing Country - Marin Golčić; Ilijan Tomaš; Aleksandra Stevanović; Goran Golčić; Renata Dobrila-Dintinjana; Suzana Erić; Mirela Šambić-Penc; Martina Baretić Marinac; Lidija Gović-Golčić; Tea Majnarić (Clinics and Practice, 2021)
Since smoking accounts for around 30% of all cancer deaths, public health campaigns often focus on smoking cessation as a means of primary prevention. However, smoking after cancer diagnosis is also associated with a higher symptom burden and lower survival rate. As data regarding smoking cessation vary dramatically between different populations, we aimed to analyze smoking prevalence in cancer patients, smoking cessation after cancer diagnosis, and the factors associated with smoking cessation in the setting of a developing country. We performed a cross-sectional survey on 695 patients in two clinical hospital centers. After cancer diagnosis, 15.6% of cancer patients stopped smoking. Male gender, younger age, and smoking-related cancer were the main factors associated with greater smoking cessation (p < 0.05). A total of 96% of breast cancer patients continued to smoke after cancer diagnosis and, compared to lung and colorectal cancer patients, exhibited a lower reduction in the number of cigarettes smoked (p = 0.023). An alarming rate of smoking prevalence was recorded in younger patients (45.6% at the time of cancer diagnosis) suggesting a future rise in smoking-related cancers and complications. These results should guide anti-smoking public health campaigns in transitional countries with a critical focus on younger and breast cancer patients.